DESAIN PEMBELAJARAN MATEMATIKA YANG MEMANFAATKAN MODEL KOOPERATIF DENGAN PENDEKATAN KONTEKSTUAL PADA KELAS XA SMK BINA GENERASI POLEWALI - Herlina Ahmad (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2014)
The problem in this research is "What is the process and result of mathematics learning design by using cooperative model with a good quality of contextual approach that meets the criteria of validity, practicality, and effectiveness?". This research included study design aimed to produce mathematic learning design with a good quality that meets the criteria of validity, practicality, and effectiveness. Learning design in this research prepared to follow the thread of development that has been made by Dick and Carey. Procedures of development design conducted by researcher performed cyclical as described by Mc Kenney which includes 3 stages: Preliminary design, Prototyping phase, and Assessment phase. The results of limit testing indicated that learning design by using cooperative model with a contextual approach is effective and practical; that is (i) the average score obtained by the students on achievement test was 74.69 from the ideal score of 100 with a standard deviation was 11.70. Where 27 of 32 students or 84.38 % met individual completeness showed that classical completeness is reached; (ii) by using learning design with cooperative model with a contextual approach, students became more active in learning process; (iii) in general, the students gave a positive response in learning activities.